Pengembangan Aplikasi Pengingat Salat Dengan Konsep Context-Aware Menggunakan MVP Pada Platform Android - Ibrahim Yunus Muhammad Fiqhan; Adam Hendra Brata; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The smartphone device is getting popular among the people. The more functionality offered by smartphones, the more difficult for people to get away of it. Because that, smarphone is very suitable as a tool to remind about the agendas owned by users. There are so many reminder apps for smartphone but the reminder still has a drawback that the app is not able to detect whether the user has performed the activities that have been scheduled. The same thing happened in the prayer reminder app. The current application of prayer reminder is only able to remind the user when entering prayer time. The application is unable to detect whether the user has performed the prayer or not. For that required context-aware concept that is expected to overcome the deficiency of the application of prayer reminder. By obtaining user-defined context information in the form of user activity obtained through existing sensors on the device, the app can determine whether the user has finished performing the prayers so that the app can provide reminders according to the user's activity. The context information used to detect user activity are the user's gender and the state of device. To get the state of the device used proximity sensor, accelerometer sensor, light sensor, and gps sensor. Implementation of this application using Model-View-Presenter (MVP) architecture that each requirements separated as a different package in which there is a view and presenter.